Influencing Mechanism of Cupping Moxibustion on Gastrointestinal Function and Immune Function in Patients with Functional Diarrhea: Cupping Moxibustion effects on Gastrointestinal and Immune Functions - Yin, Cuiying; Fang, Ying; Yao, Dan; Zhang, Xiaojing (Cellular and Molecular Biology, 2022)
it was aimed to investigate the efficacy and safety of cupping moxibustion in patients with functional diarrhea. 51 patients diagnosed with functional diarrhea from January 2021 to December 2021 were selected as the objects, and they were randomly divided into the control group (oral montmorillonite powder) and the experiment group (oral montmorillonite powder combined with cupping moxibustion). The number of diarrheas, Bristol stool, traditional Chinese medicine (TCM) syndromes, clinical efficacy indexes, self-rating anxiety scale (SAS) score, the MOS item short from health survey (SF-36) scale score, peripheral blood cell levels of CD4+, CD8+, and Th17, gastrin (GAS), motilin (MTL), and cholecystokinin (CCK) levels was assessed before and after treatment. The adverse events were also recorded. Compared with those before treatment, all indexes of both groups were significantly improved (P<0.05). Compared with those of the control group, the number of diarrheas, Bristol stool, TCM syndrome score, SAS score, and CD8+ cell levels was significantly decreased after treatment in the experiment group (P<0.05). The clinical cure rate (48.0% vs. 73.1%), SF-36 score, GAS, MTL, CCK contents, and CD4+, and Th17 cell levels were significantly increased (P<0.05). No significant difference was in the incidence of adverse events between the two groups (P>0.05). It could be suggested that cupping moxibustion could be applied in the treatment of functional diarrhea, improving the clinical symptoms, relieving anxiety, enhancing gastrointestinal and immune functions, and promoting the quality of life of patients significantly.